PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI MTS DARUNNAJAH 2 CIPINING BOGOR - Dwi Kusuma Wardani; Muhammad Mukhlis Nasrullah; Nur Rochmat; Ahmad Farid Farid (CV. ALIM'SPUBLISHING, 2023)
Abstract. This research approach uses quantitative methods. The population of this study was all students of class IX MTs Darunnajah 2 Cipining Bogor which consisted of 7 classes with a total of 225 students. The sampling technique in this study used Simple Random Sampling, namely the class that became the sample was class IX E-IX J and IX L as many as 34 students. The data collection technique is using a questionnaire. The data analysis technique used is simple linear regression. It is known that the results of statistical calculations using SPSS 22 show the results of research that there is an influence between teacher pedagogic competence (X) on student learning interest (Y) at MTs Darunnajah 2 Cipining, it is proven that the results of the coefficient of determination in the summary model table value R square = 0.202, to determine the amount the effect of variable x on variable y is 20%. So the results of the coefficient of determination show that 20% of the teacher's pedagogic competence contributes to student interest in learning, while the remaining 100% - 20% = 80% is influenced by other factors. Keywords: Teacher Pedagogic Competence, Student Interests, Citizenship Education.